(untitled) (Journal of Economic Research & Business Administration, 2016)
Information necessary for control andcomparison of actual re-sults with плановыми is formed inan administrative account, on struc-tural subdivisions andsegments of organization, and also for the accep-tance ofdifferent administrative decisions, planning and estimationof al-ternative variants of actions. For the acceptance of different operative economicdecisions man-agers and leaders need reliable information,both about produc-tive and about financial position ofenterprise. Exactly it served princi-pal reason of selection ofadministrative account as an independent ele-ment of thesystem of record-keeping.